Analisis Seri Kasus Pseudoaneurysm Setelah Trauma Ginjal Tumpul pada Tahun 2016-2020 - Arifah Zanuar Kumalasari; Agus Sudaryanto (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
Introduction: Renal trauma occurs about 1-5% of all trauma events and about 10% of patients experience abdominal tarauma. Pseudoaneurysm is a vascular complication that rarely occurs after blunt trauma. The purpose of this paper is to analyze pseudoaneurysm cases after blunt kidney trauma. Method: The design used in the study literature uses a literature review design. The analysis used by the writer is a narrative review analysis. Search for articles using PubMed and Google Scholar according to the chosen theme then do a review. Results: Of the 5 articles that experienced pseudoaneurysm after blunt kidney injury suffered the most in men. Four cases were caused due to falls. Signs and symptoms of five cases are decreased blood hemoglobin levels and gross hematuria. Four cases had blunt kidney trauma on the right side and the CT scan showed 3 cases in grade III. Discussion: Among adults who are often found are men at productive age. A person's age is a risk factor for pseudoaneurysm after blunt kidney injury. Hematocrit examination accompanied by examination of blood hemoglobin plays a role in identifying signs of active bleeding that are suspected of having decreased hemoglobin levels. Conclusion: Analysis of the five articles found a sign of gross hematuria and a decrease in blood hemoglobin levels and a medical treatment that is often used is embolization. Keywords: Pseudoaneurysm, Kidney, Blunt Trauma, Embolization, Analysis.